211PAdjuvant axitinib in Asian vs non-Asian patients with metastatic renal cell carcinoma (mRCC): ATLAS trial subgroup analysis. (24th November 2019) - Ng, C F; Kwon, T G; Eto, M; Miyake, H; Seo, S I; Byun, S-S; Lee, J L; Rosbrook, B; Grande, E; Gross-Goupil, M; Quinn, D I
Abstract: Background: The ATLAS trial compared axitinib (AXI) vs placebo in patients (pts) with locoregional renal cell carcinoma at risk of recurrence after nephrectomy. ATLAS was stopped due to futility at a pre-planned interim analysis. A subgroup analysis was performed to describe differences between Asian vs Non-Asian pts and different Asian groups by geography in baseline characteristics and safety. Methods: The exploratory subgroup analysis population included 363 pts randomized to receive AXI and 361 randomized to placebo. The primary endpoint was disease-free survival (DFS). Results: DFS had the largest treatment effect in highest risk pts for Asian and Non-Asian pts: Hazard ratio = 0.731 (Asians) vs. 0.755 (Non-Asians). A similar trend was noted for Fuhrman Grade 3-4. Additional key results from the analysis are presented in the table. AE=adverse events Asian pts on AXI had higher frequencies of proteinuria, hypothyroidism, and nasopharyngitis and lower frequencies of fatigue and asthenia compared to Non-Asian pts on AXI. Within major Asian groups, proteinuria, hypothyroidism, nasopharyngitis and hypertension were more common in Japanese > Korean > Chinese pts. Conclusions: DFS did not vary based on ethnicity. Asian pts had a lower median daily dose, and more frequent dose reduction vs non-Asian pts. More Asian pts had AEs leading to dose reductions of AXI and study withdrawals vs non-Asian pts. There were notable differences in AEs between Asian and Non-Asian pts and between Japanese, Korean and Chinese pts. Clinical trial identification: NCT01599754. Editorial acknowledgement: The study is sponsored by Pfizer. Medical writing support was provided by Charles Cheng, MS, of Engage Scientific Solutions, and funded by Pfizer. Legal entity responsible for the study: This study was sponsored by Pfizer Inc and SFJ Pharmaceuticals. Funding: This study was sponsored by Pfizer Inc and SFJ Pharmaceuticals. Disclosure: C.F. Ng: Advisory / Consultancy, Speaker Bureau / Expert testimony: Boston Scientific; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Janssen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Astellas; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Ferring; Speaker Bureau / Expert testimony: Amgen; Research grant / Funding (institution): Olympus. T.G. Kwon: Research grant / Funding (institution): Kyungpook National University Chilgok Hospital. M. Eto: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): ONO; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self): Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Speaker Bureau / Expert testimony: Bayer. S.I. Seo: Honoraria (self): Ipsen; Honoraria (self): Pfizer; Research grant / Funding (self): Alvogen. B. Rosbrook: Shareholder / Stockholder / Stock options, Full / Part-time employment: Pfizer. E. Grande: Honoraria (self), Research grant / Funding (self): Pfizer; Honoraria (self): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (self): IPSEN; Honoraria (self), Research grant / Funding (self): Roche; Honoraria (self): Eisai; Honoraria (self): Eusa Pharma; Honoraria (self): MSD; Honoraria (self): Sanofi-Genzyme; Honoraria (self): Adacap; Honoraria (self): Novartis; Honoraria (self): Pierre Fabre; Honoraria (self), Research grant / Funding (self): Lexicon; Honoraria (self): Celgene; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): MTEM/Threshold. M. Gross-Goupil: Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: BMS; Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: MSD; Advisory / Consultancy, Research grant / Funding (self): Ipsen; Advisory / Consultancy, Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Amgen. D.I. Quinn: Advisory / Consultancy: Pfizer; Advisory / Consultancy: Bayer; Advisory / Consultancy: Novartis; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy: Merck; Advisory / Consultancy: Exelixis; Advisory / Consultancy: Genentech; Advisory / Consultancy: Roche; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Astellas. All other authors have declared no conflicts of interest.